Development and Characterization of Sr-Containing Glass-Ceramic Composites Based on Biogenic Hydroxyapatite - Kuda, Oleksii (Nanoscale Res Lett, 2018)
Composite materials based on hydroxyapatite are widely used for bone tissue engineering. There is evidence of a positive effect of the presence of strontium in osteoplastic materials in the case of a Ca/Sr certain ratio. To examine the effect of the addition of Sr(2+), a study was made by introducing it into the material composition based on biogenic hydroxyapatite and sodium borosilicate glass (50/50% wt.). The strontium was introduced into the composition in an amount of 1% wt. Composite materials were obtained at final sintering temperatures of 780 °C and a sintering time of 1 h. The effect of additions of glass phase and strontium affect changes in the crystal lattice of biogenic hydroxyapatite was investigated with the help of X-ray phase analysis, IR spectroscopy. Also the behavior of composites in vitro in physiological solution was studied.